Demographic and clinical characteristics of cytomegalovirus reactivation in dermatomyositis. Issue 8 (26th May 2020) - Sekiguchi, Akiko; Inoue, Yuta; Yamazaki, Sahori; Uchiyama, Akihiko; Endo, Yukie; Ishikawa, Osamu; Motegi, Sei‐ichiro
Abstract: Dermatomyositis (DM) patients are known to have various infectious complications, such as cytomegalovirus (CMV) reactivation, due to immune dysfunction caused by DM itself and immunosuppressants used for treatment. Although CMV reactivation has been known to be a major cause of mortality in immunocompromised hosts, there has not been sufficient study of CMV reactivation in DM patients. The objective of this study was to examine the frequency of CMV reactivation in DM patients and to investigate risk factors potentially associated with development of CMV reactivation. We analyzed 52 Japanese DM patients, and CMV reactivation was observed in 21 (40.4%). The mean duration from the initiation of prednisolone (PSL) to the diagnosis of CMV reactivation was 6.1 ± 0.5 weeks. The total amount of oral PSL before the diagnosis of CMV reactivation was 2000.3 ± 169.3 mg. Using a univariate analysis, we found that the prevalence of interstitial lung disease and the frequency of diabetes mellitus complications in DM patients with CMV reactivation was significantly higher than that in DM patients without CMV. We identified that low lymphocytes (<900/μL) in DM patients was significantly associated with developing CMV reactivation. The use of immunosuppressants, including tacrolimus, cyclosporin and/or i.v. cyclophosphamide, was significantly associated with CMV reactivation in DM patients. Using a multivariate analysis, low lymphocytes at the time of DM diagnosis was found to be a risk factor for CMV reactivation. In addition, there was a tendency for diabetes mellitus to be a risk factor for CMV reactivation in DM patients. There was no difference in the prognosis for those with or without CMV reactivation in this study. These results suggest that in the DM patients with risk factors such as low lymphocytes and diabetes mellitus complications, regularly monitoring CMV reactivation and adequate treatment with antiviral agents may be necessary to prevent a poor prognosis.